A microfluidic paper-based analytical device (μPAD) with smartphone readout for chlorpyrifos-oxon screening in human serum - Tsagkaris, A S; Migliorelli, D; Uttl, L; Filippini, D; Pulkrabova, J; Hajslova, J (Talanta, 2021)
Acute intoxication incidents due to neurotoxic organophosphate (OP) insecticides are occasionally reported, related either to suicidal attempts or occupational exposure due to the misuse of protective equipment. Among them, chlorpyrifos is a compound related to great controversy, which is still authorized and easily accessible in many countries around the world. However, to screen for its exposure markers, instrumental methods are commonly applied, which cannot enable rapid monitoring at an early stage of an intoxication. Therefore, in this study, a microfluidic paper-based analytical device (μPAD) able to rapidly screen for chlorpyrifos-oxon, the toxic chlorpyrifos metabolite, in human serum was developed and fully validated. The μPAD combines wax-printed butyrylcholinesterase (BChE) paper sensors, a lab-on-a-chip (LOC) prototype injector and a smartphone as the analytical detector. In principle, the wax-printed strips with adsorbed BChE are embedded into LOC injectors able to deliver samples and reagents on-demand. A smartphone reader was used to monitor the color development on the strips providing binary qualitative results. μPAD method performance characteristics were thoroughly evaluated in terms of specificity, detection capability (CCβ) and ruggedness. The developed analytical platform is rapid (results within 10 min), cost-efficient (0.70 €), potentially applicable at the point-of-need and attained a low CCβ (10 μg L-1 in human serum). Finally, μPAD characteristics were critically compared to well-established methods, namely an in-house BChE microplate assay and liquid chromatography tandem mass spectrometry.
Keywords: Paper; Smartphone; Microfluidic Analytical Techniques; Humans; Lab-On-A-Chip Devices; Chlorpyrifos-oxon; lidé; papír; dursban; Microfluidic paper-based analytical device; chytrý telefon; laboratoř na čipu; Smartphone readout; mikrofluidika; Lab-on-a-chip; mikrofluidní analytické techniky; Chlorpyrifos; Microfluidics; Wax-printing